2016
DOI: 10.18178/ijoee.4.1.37-41
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Modified Vertical Axis Tidal Turbine to Improve Lift Performance

Abstract: A design of Darrieus vertical axis tidal turbine using modified airfoil was studied numerically in this work. The turbine design was evaluated in 2D CFD model using kω turbulence model, upwind interpolation scheme and simulated using OpenFOAM. The turbine had three blades which were arranged symmetrically. The blades were of NACA 0012 airfoil which had been modified in the trailing edge region to increase its lift performance. The modification was made by truncating the trailing edge at the 15% of chord length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Many attempts have been made to improve the straight-blade vertical axis ocean current turbine performance by modifying the foil, blade, and rotor. Arini et al [12] have carried out research with modifi ed foil and showed it can increase lift performance by 12% by cutting the trailing edge of the foil. Analysis by modifying blades has been carried out for the fi rst time by Gorlov [13], and the results show that it can increase the maximum power coeffi cient up to 0.35 by changing the shape of a straight blade into a helical blade.…”
Section: Introduction / Uvodmentioning
confidence: 99%
“…Many attempts have been made to improve the straight-blade vertical axis ocean current turbine performance by modifying the foil, blade, and rotor. Arini et al [12] have carried out research with modifi ed foil and showed it can increase lift performance by 12% by cutting the trailing edge of the foil. Analysis by modifying blades has been carried out for the fi rst time by Gorlov [13], and the results show that it can increase the maximum power coeffi cient up to 0.35 by changing the shape of a straight blade into a helical blade.…”
Section: Introduction / Uvodmentioning
confidence: 99%
“…Ref. [21] adopts the two shapes to study the influence on turbine performance under the conditions of R e of 3 million and the SST k-omega turbulence model, but the influence on the simulation accuracy of NACA0012 force coefficients is not analyzed. Ref.…”
Section: Introductionmentioning
confidence: 99%